2019
DOI: 10.1080/00076791.2019.1592157
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural factors in international branding

Abstract: This is the second special issue resulting from the symposium titled 'The Brand and Its History'. This issue aims at deepening the knowledge of the historical and cultural roots of the origin, uses, and meanings of modern branding. This editorial summarises previous contributions from economic, marketing, and historical literature; presents the main findings of the seven articles included in this issue; and reflects on possible further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…The interest in trademarks was largely driven by the recognition that trademarks are the type of IPR most pervasive globally (Zolas et al, 2017) and that, especially in developing and middle-income countries, companies rely more on trademarks than patents (Azomahou & Diene, 2012; Kang et al, 2020;Lee et al, 2021). In several history-oriented and geography-sensitive works, Lopes (2005Lopes ( , 2016 and Castro and Sáiz (2020) have also shown how multinational business success can be derived from locally developed trademark-intensive strategies in a variety of sectors.…”
Section: Trademarks and Regional Paths Of Specialization/diversificationmentioning
confidence: 99%
“…The interest in trademarks was largely driven by the recognition that trademarks are the type of IPR most pervasive globally (Zolas et al, 2017) and that, especially in developing and middle-income countries, companies rely more on trademarks than patents (Azomahou & Diene, 2012; Kang et al, 2020;Lee et al, 2021). In several history-oriented and geography-sensitive works, Lopes (2005Lopes ( , 2016 and Castro and Sáiz (2020) have also shown how multinational business success can be derived from locally developed trademark-intensive strategies in a variety of sectors.…”
Section: Trademarks and Regional Paths Of Specialization/diversificationmentioning
confidence: 99%
“…1 However, in the 1990s some relevant studies on the development of brands already appeared, such as the works included in the book edited by Jones and Morgan (1994) or the articles of Wilkins (1992) and Higgins and Tweedale (1995). A historiographic review of the research on brands is found in Sáiz and Castro (2018) and in Castro and Sáiz (2020).…”
Section: Notesmentioning
confidence: 99%
“…Although the development of brands has been a topic traditionally little studied in Business History (Duguid, da Silva & Mercier, 2010, p. 17) 1 , there has been considerable progress in research on the subject since the beginning of the 21st century (Da Duguid, 2010 and2012;Sáiz and Castro, 2018;Castro and Sáiz, 2020). In Spain, the works of Sáiz and Fernández have been fundamental Fernández, 2009 and2012).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, cultural influences on buying behaviour are to the extent that consumers often display these influences in the values they pick from the society (Fahimeh et al, 2016). Such cultural values affect marketing decisions on the marketing mix elements (Castro and Sáiz, 2020). However, many people in this world live within societies in which group's interest takes precedence and interest over individuals interest (Hofstede et al, 2010).…”
mentioning
confidence: 99%